The Kano Model: How the Pandemic Influences Customer Satisfaction with Digital Wallet Services in Indonesia - Vanesa Hana Budiarani; Rahmat Maulidan; Diki Putra Setianto; Ipuk Widayanti (Faculty of Economics and Business, Universitas Gadjah Mada, 2021)
Introduction/Main Objectives: This study aims to evaluate the effectiveness of digital wallets service qualities using Kano Model. Understanding customer needs and satisfaction is crucial in developing products. Background Problems: In the “new normal” era, payment method is predicted to shift to digital wallets. For quality improvement, digital wallet companies should understand customer needs and satisfaction. This study used the Kano model to analyze customer needs and satisfaction in OVO and ShopeePay, two digital wallets widely used for online shopping transactions during COVID19. Novelty: Although studies into the Kano model implementation towards e-commerce exist, there are no specific studies on the model implementation concerning digital wallet payments amid COVID-19. The Kano model is significant in understanding which software products generate high customer satisfaction, which will give a greater influence, as well as necessary attributes for the customers. Research Methods: This study employed the Kano model as one of the most relevant method to measure customer satisfaction by measured of each attribute’s quality. Finding/Results: Most features of OVO and ShopeePay are categorized into the “must be” and “one dimensional” category. The satisfaction map results indicate that most items placed in the “indifferent” quadrant denote the unfulfilled customer expectations. Conclusion: OVO and ShopeePay should improve the items placed in the “indifferent” quadrant first. This study contributes empirically and theoretically by emphasizing the Kano model’s utility for digital wallet services and providing new insights for digital wallet companies and the government on Indonesians’ usage of digital wallets in the “new normal”.